Pengaruh Lampau Waktu Terhadap Gugatan - Nurun Ainuddin (Fakultas Hukum Universitas Mataram, 2015)
This research is aliteraturestudies that conductedsolely basedonwritten work, includingeither published research or not published research.This studydoes notdirectlygo to the fieldin search ofthe source data butcan be doneat home, in the libraryandotherplaces.The objectivesofthis study were (1) To provethatthe effect oftheexpiryof thelawsuitis a vitalcommunity needs, (2) To provethatthe effect ofexpiryoftenlead tolegal problemsand mostly ends in the court roomand(3) Toknow how far thegovernment's effortsto regulate expiry,through regulationsandlegislationin thevarious policies.Asresults to be achievedishow far the right of substitutionby the plaintiffinthe casecan be decidedby a judgeto becompletelyfair. The conclusion ofthis studyis theEffect ofexpiry,resulting inalawsuitwhich oftenled to disputesin all circles. This should beevaluated fromcase to caseandis alwaysconsideredthe development ofthe communitywhere the caseoccurred.